Induksi Tunas Beberapa Varietas Nilam (Pogostemon cablin Benth.) dan Konsentrasi BAP Secara In Vitro Shoot Induction of Several Varieties of Patchouli (Pogostemon cablin Benth.) and Concentration of BAP In Vitro - Amalia, Firda; Basyah, Bakhtiar; Kesumawati, Elly (Universitas Teuku Umar, 2023)
Conventional propagation of patchouli plants has not met the demand for superior seeds. Propagation of superior seeds in a relatively short time can be done using in vitro culture techniques. This research aims to determine the induction of patchouli shoots of Tapaktuan, Lhokseumawe and Sidikalang varieties with Benzyl Amino Purine (BAP) concentrations in vitro. This research was carried out at the Plant Tissue Culture Laboratory, Faculty of Agriculture, Syiah Kuala University. This research used a Randomized Block Design with a 3x4 factorial pattern consisting of 2 factors. The first factor was patchouli variety which consisted of 3 levels, namely: Tapaktuan, Lhokseumawe, and Sidikalang. The second factor was BAP concentration which consisted of 4 levels, namely: 0 (control), 0.5, 1, and 1.5 mg L-1. The results showed that the percentage of live patchouli explants was 100% in all treatments. The time and percentage of shoot emergence tended to be faster in the Lhokseumawe + BAP 0.5 mgL-1, namely 17.5 days after planting (DAP) and 100%. The number of patchouli explant shoots tended to be high in the Sidikalang + BAP 0.5 mgL-1, namely 12 shoots. The number of patchouli explant leaves tended to be high in the Lhokseumawe + BAP 1 mgL-1, namely 13 sheets. Patchouli explants tended to be taller in the Sidikalang + control, namely 8 cm. The percentage of callus formation tends to be high in the varieties Tapaktuan + BAP 1 mgL-1, Sidikalang + BAP 0.5 mgL-1, Sidikalang + BAP 1 mgL-1, Tapaktuan + BAP 1.5 mgL-1, Sidikalang + BAP 1.5 mgL-1 and Sidikalang + control were above 50% at 4 WAP. The number of patchouli explant roots tended to be high in the Tapaktuan + control, namely 16.50 roots. Keywords: Aceh Patchouli, BAP, Cytokinin, Explant, Patchouli Shoots